Local Wisdom Values on Customary Law Norms of the Jambi Malay Seloko Adat - Ade Rahima; Erlina Zahar (Umbara, 2022)
This study aims to describe local wisdom values on customary law norms of the Jambi Malay oral tradition containing moral guidance named Seloko Adat. This study applied descriptive qualitative design. Data were collected through archival studies on Seloko Adat and interviews. Content analysis integrated with structural hermeneutics were applied to the data analysis. Findings of this study suggests that Seloko Adat contains guidance on customary law and were loaded with local wisdoms values which depict the five basic principles of customary law, that are: 1) customary law which is derived from the Holy Qur’an and Hadith; 2) customary law which is based on the old traditions which is derived from empirical evidences about truth or goodness to protecting the society; 3) customary law based on justice and fairness; 4) customary law about adhering to the truth; and 5) customary law based on deliberation and consensus.